The Relationship Between Social Comparison on Instagram and Self-Esteem among Emerging Adults in Indonesia - Amelia Christin Sitorus; Vania Ardelia (STAI Auliaurrasyidin Tembilahan, 2026)
This study aims to examine the relationship between social comparison and self-esteem among emerging adults who use Instagram. This study employed a quantitative correlational design involving 200 emerging adults aged 18–25 years who actively use Instagram. The instruments used were the Iowa–Netherlands Comparison Orientation Measure (INCOM) to assess social comparison and the Rosenberg Self-Esteem Scale (RSES) to measure self-esteem. Reliability analysis indicated good internal consistency for both scales (α = 0.737 for social comparison and α = 0.711 for self-esteem). Normality testing showed that the data were normally distributed (p > 0.5). Pearson correlation analysis revealed a significant negative relationship between social comparison and self-esteem (r = -0.206, p = .004). Although statistically significant, the correlation coefficient indicated a small effect size, suggesting that social comparison explained only a limited proportion of variance in self-esteem. These findings indicate that higher social comparison is associated with lower self-esteem. This study contributes to the literature by investigating the relationship between social comparison and self-esteem among Indonesian emerging adults who use Instagram through standardized psychological instruments. The findings suggest that social comparison activities on Instagram contributes to self-evaluation processes among emerging adults. Furthermore, the study extendes the theoretical understanding of self-esteem development during emerging adulthood and provides practical implications for promoting healthier social media use to support psychological well-being.